When the going gets tough, the tough get going - Fredriksson, A.; Maresch, D.; Fink, M.; Moro, Andrea (Pepperdine University, Graziado School of Business and Management, 2017)
A bank’s lending decision is affected by the amount of information it can access and by its capability to manage this information. The latter aspect implies that the bank has to decide whether borrowers should be managed in a local branch of the bank or in its headquarters. By looking at a sample of Finnish banks, the present research investigates a bank’s capability to extract profitability from both locally and centrally managed firms. We find that banks are able to properly discriminate between firms: those which should be managed by loan managers with expert knowledge in the bank’s headquarters due to their complexity, and those firms which should be managed in the bank’s local branch because they are simpler and need standard products and services. As a result, banks are able to extract risk-adjusted profitability (RAP) from both centrally and locally managed customers. Our findings clearly support the argument that the decision to centralise or decentralise the lending decision process is not an either/or decision: banks should implement both approaches and apply according to the type of firm they serve.
Keywords: Small Firms; Local Banks; Transaction Lending; Relationship Lending Risk- Adjusted Profitability